Transformasi Digital UMKM dan Implikasinya terhadap Pertumbuhan Ekonomi, Inflasi, dan Pengentasan Kemiskinan: Kajian Konseptual - Mentalita, Hotma; Menari Sitohang (CV. ULIL ALBAB CORP, 2025)
Digital transformation of Micro, Small, and Medium Enterprises (MSMEs) is increasingly recognized as a crucial catalyst for economic progress in developing nations, including Indonesia. This conceptual article explores the interconnections between MSME digitalization, economic growth, inflation, and poverty reduction through a comprehensive literature review. Findings indicate that adopting digital technologies can enhance productivity, broaden market access, and strengthen financial inclusion. Improved MSME performance, in turn, fosters inclusive growth. Furthermore, digital integration has the potential to influence inflation through efficiency in distribution and price transparency, while also playing a significant role in reducing poverty by generating employment opportunities and increasing household income. The study underscores the need for coordinated policies among governments, financial institutions, and business actors to maximize the benefits of MSME digitalization as a pathway to sustainable development.